Stress and coping connected to higher education study structures: combined views from teachers and students - Eija-Liisa Heikka; Pia Hurmelinna-Laukkanen; Outi Keränen; Pia Partanen (Finnish Social and Health Informatics Association, 2023)
Experienced stress by students and teachers in higher education has attracted increasing interest, but the two groups are rarely studied together. We combine their perspectives by considering the stress and coping among students and teachers concerning the development of study structures in a business school context. The findings indicate a strong connection between stress experienced by students and teachers, reflecting their interactive nature in this context. We categorize factors causing stress to those for which effective coping mechanisms exist, those causing tensions and requiring active management, and stressors that are difficult to remove because a coping mechanism for one group increases the stress of the other. Our findings add to existing knowledge on stress and coping mechanisms in higher education by combining the perspectives of students and teachers concerning study structures in business education.